Early rheumatoid arthritis therapy: comparative characteristic of delagil, sulphasalazine and methotrexate - T S Salnikova; R M Balabanova (Научно-практическая ревматология, 2003)
Objective. To assess early administration and efficacy of 3 disease modifying antirheumatic drugs. Material and methods. 92 pts with rheumatoid arthritis (RA) aged 17 to 45 years (mean age 34,9±8,5 years) were included. Disease duration did not exceed 6 months (mean 3,5±1,9 months. All had 2-3 activity degree and did not received glucocorticoid therapy (systemic or local) and did not have severe concomitant diseases of internal organs. Results. Diagnosis of RA was confirmed during follow up in 90 pts. In 2 pts after 6 months diagnosis was changed to systemic lupus erythematosus. 30 pts received delagil for 3 months without improvement. Treatment with sulphasalazine for 3 months was not effective in 23 from 30 pts. 7 pts had subjective improvement during first 3 months but at 6 month effect was lost. Methotrexate administration provided improvement (DAS change 1,6). Clinical and laboratory remission was achieved in 6 pts. Number of bone erosions in pts treated with methotrexate was significantly less and depended on time of therapy beginning and features of disease onset. Conclusion. Methotrexate was most effective from the 3 drugs in early RA particularly when administered during first 3 months of the disease.